Epidemiological Features of the COVID-19 and Characteristics of Patients during the Spread of the Omicron SARS-COV-2 in Russia - A. A. Fomicheva; N. N. Pimenov; S. V. Komarova; A. V. Urtikov; N. N. Tsapkova; A. R. Sakhautdinov; D. A. Strelkova; G. V. Nekludova; S. A. Rachina; S. N. Avdeev; V. P. Chulanov (Эпидемиология и вакцинопрофилактика, 2024)
Aim. To analyze dynamic of incidence and mortality of COVID-19 and clinical and epidemiological characteristics of adult patients with a new coronavirus infection during the early period of the Omicron SARS-COV-2 distribution in Russia. Materials and Methods. We conducted a retrospective analysis of the dynamics of COVID-19 incidence and mortality in Russia until 2023. Study included patients aged ≥18 years with a laboratory-confirmed diagnosis of COVID-19, detected in the period from 01/02/2022 to 14/03/2022 (n = 3 582 688) in 85 regions of Russia. Participants were included regardless their COVID-19 vaccination history. Results. We identified 6 periods of rise and decline in the COVID-19 incidence until 2023 in Russia. The 5th (January–July 2022) and the 6th (August-November 2022) periods were associated with the spread of the Omicron SARS-CoV-2. The median age of patients in the early period of Omicron spreading was 49 (36–62) years, 62.7% were women. The largest proportion of patients were represented by the age groups 30–39 and 40–49 years (19.2% each), the lowest – 18–29 years (12.3%). Proportion of patients with mild disease was 90.0%, moderate – 8.5%, severe – 0.9%, extremely severe – 0.6%. Hospitalization rate, proportion of patients treated in the intensive care unit and rate of invasive mechanical ventilation were 7.6%, 9.5% and 6.7% respectively. The median period from the onset of symptoms to the diagnosis was 2 (1–3) days, median of duration of the disease was 8 (6-10) days and median duration of hospitalization was 10 (7–14) days. The median age of the deceased patients was 77 (69–84) years, of which 50.8% were women, 72.6% were persons ≥70 years old. One or more concomitant diseases were detected among 8.7% of patients who became ill and 75.8% of those who died. The probability of hospitalization, admission to the ICU, IMV and death in patients with one or more concomitant diseases were 24.5, 3.2, 3.5 and 35.8 times higher, respectively, compared with patients without concomitant diseases. Conclusion. In the early period of the spread of the Omicron variant in Russia, among adult patients with COVID-19, excluding their vaccine history, the frequency of severe and extremely severe forms of infection was 1.5%. The elderly age and the presence of concomitant diseases remained key risk factors for the development of adverse outcomes of the COVID-19